2011
DOI: 10.1097/qai.0b013e3182303921
|View full text |Cite
|
Sign up to set email alerts
|

Providing Immediate CD4 Count Results at HIV Testing Improves ART Initiation

Abstract: Receipt of a CD4 count at the time of HIV testing increases ART initiation rates. Point-of-care diagnostics can be used to improve retention, but losses to pre-ART care remain high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 13 publications
4
98
0
Order By: Relevance
“…42,43 Studies of POC CD4 count tests have demonstrated good agreement with lab-based testing, 4449 and two studies have demonstrated accelerated time to antiretroviral therapy initiation and a higher rate of people initiating antiretroviral therapy. 50,51 Novel POC tests for pulmonary tuberculosis have shown promising sensitivity for detecting disease, 5254 and Xpert MTB/RIF testing accelerated time to treatment for smear-negative tuberculosis. 55 A POC test for Plasmodium falciparum malaria demonstrated good agreement with thick smear microscopy, 56,57 while reducing overdiagnosis of malaria among children presenting with fevers.…”
Section: Studies Of Point-of-care Tests In Resource-limited Settingsmentioning
confidence: 99%
“…42,43 Studies of POC CD4 count tests have demonstrated good agreement with lab-based testing, 4449 and two studies have demonstrated accelerated time to antiretroviral therapy initiation and a higher rate of people initiating antiretroviral therapy. 50,51 Novel POC tests for pulmonary tuberculosis have shown promising sensitivity for detecting disease, 5254 and Xpert MTB/RIF testing accelerated time to treatment for smear-negative tuberculosis. 55 A POC test for Plasmodium falciparum malaria demonstrated good agreement with thick smear microscopy, 56,57 while reducing overdiagnosis of malaria among children presenting with fevers.…”
Section: Studies Of Point-of-care Tests In Resource-limited Settingsmentioning
confidence: 99%
“…The type of HIV test used for the study population was not specified in one study (38). Although two studies reported on the impact of POC diagnostics on HIV-infected women, the maternal status of these women was not reported and the impact of POC diagnostics on maternal outcomes could not be determined (39, 40). …”
Section: Resultsmentioning
confidence: 99%
“…CD4 count testing is specifically aimed at improving the health outcomes of HIV infected patients by enabling the determination of the clinical staging of the appropriate ART regime (39). The WHO B+ approach advocates for all pregnant and breastfeeding woman who test HIV-positive to be initiated on the lifelong antiretroviral therapy (ART), regardless of CD4 count or clinical staging (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prompt availability of CD4 test results has been demonstrated to increase ART initiation and retention of patients in care [26,27].…”
Section: Technologies For Disease Staging and Treatment Monitoring CDmentioning
confidence: 99%